Combining phenomics with transcriptomics reveals cell-type-specific morphological and molecular signatures of the 22q11.2 deletion - Matthew Tegtmeyer; Dhara Liyanage; Yu Han; Kathryn B. Hebert; Ruifan Pei; Gregory P. Way; Pearl V. Ryder; Derek Hawes; Callum Tromans-Coia; Beth A. Cimini; Anne E. Carpenter; Shantanu Singh; et al. (Nature Communications)
Abstract Neuropsychiatric disorders remain difficult to treat due to complex and poorly understood mechanisms. NeuroPainting is a high-content morphological profiling assay based on Cell Painting and optimized for human stem cell–derived neural cell types, including neurons, progenitors, and astrocytes. The assay quantifies over 4000 features of cell structure and organelle organization, generating a dataset suitable for phenotypic screening in neural models. Here, we show that, in studies of the 22q11.2 deletion—a strong genetic risk factor for schizophrenia—we observe cell-type-specific effects, particularly in astrocytes, including mitochondrial disruption, altered endoplasmic reticulum organization, and cytoskeletal changes. Transcriptomic analysis shows reduced expression of cell adhesion genes in deletion astrocytes, consistent with post-mortem brain data. Integration of RNA and morphology data suggests a link between adhesion gene dysregulation and mitochondrial abnormalities. These results illustrate how combining image-based profiling with gene expression analysis can reveal cellular mechanisms associated with genetic risk in neuropsychiatric disease.